Evidence-based medicine (EBM) and occupational health surveillance: A review of the principles and experiences in occupational health - Francesco CHIRICO; Angelo SACCO; Nicola MAGNAVITA (GIornale Italiano di Psicologia e Medicina del Lavoro, 2022)
Evidence-Based Medicine (EBM) is the conscientious, explicit, judicious, and reasonable use of up-to-date best evidence in making decisions about the care of individuals. Narrative-Based Medicine (NBM) is a new model that postulates the application of narrative ideas and new ways of communication to the practice of medicine. Occupational physicians should apply both principles in workplace activities-. The health surveillance activity, which does not produce randomized controlled trials (RCTs) because exposing workers to risk would not be ethical, will be based on evidence obtained from systematic reviews and meta-analyses, according to EBM principles. However, qualitative or mixed-design methods research following the NBM principles can be appropriate for understanding complex interactions, behavioral, and social predictors of risk factors and conditions affecting the effectiveness of preventive measures. In this commentary, the authors describe how to apply EBM and NBM in occupational health surveillance.